Pengembangan Media Papan Berhitung (Patung) pada Materi Pokok Penjumlahan untuk Siswa Kelas I - Rahayu sofiana; Rosidah Aliim Hidayat; Mahmudah Titi Muanifah (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to (1) describe the development of counting board media, (2) describe the feasibility of counting board media. The Research and Development (R&D) research method was carried out at SDN 160/VIII Sidorukun using a sequence of media development combining the theories of Borg and Gall and Sugiyono, namely: (1) research and data collection, (2) planning, (3) product design, ( 4) design validation, and (5) design revision. Data collection techniques used include observation, interviews, questionnaires and documentation. The data analysis technique used is descriptive analysis technique by determining the average score of the questionnaire. Before being tested, the counting board media was validated by 3 validators which included material expert validators, media experts and linguists.The results of media validation by material experts and linguists are included in the very valid category (SV) while those by media experts are included in the Valid category (V). While the results of small and large scale trials can be said to be practical in its implementation. Based on this, the counting board media product has met the eligibility criteria, namely validity and practicality.